Software engineering ontology - the instance knowledge (Part I) - Wongthongtham, Pornpit; Chang, Elizabeth; Dillon, Tharam S.; Sommerville, I. (Emerald Publishing, 2007)
The software engineering ontology defines common sharable software engineering knowledge including particular project information. Reaching a consensus of understanding is of benefit in a distributed multi-site software development environment. Software engineering knowledge is represented in the software engineering ontology whose instantiations are undergoing evolution. Software engineering ontology instantiations signify project information which is shared and has evolved to reflect project development, changes in software requirements or in the design process, to incorporate additional functionality to systems or to allow incremental improvement, etc. This evolution of instances provides many new challenges to an ability to design and deliver project information. In this paper, we present development of application tools to facilitate software engineering ontology instantiations management.